The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/jp506637v
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Isophorone with Pd(111): A Combination of Infrared Reflection–Absorption Spectroscopy, Near-Edge X-ray Absorption Fine Structure, and Density Functional Theory Studies

Abstract: Atomistic level understanding of interaction of α,β-unsaturated carbonyls with late transition metals is a key prerequisite for rational design of new catalytic materials with the desired selectivity toward C=C or C=O bond hydrogenation. The interaction of this class of compounds with transition metals was investigated on α,β-unsaturated ketone isophorone on Pd(111) as a prototypical system. In this study, infrared reflection–absorption spectroscopy (IRAS), near-edge X-ray absorption fine structure (NEXAFS) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In our recent studies on hydrogenation of the simple carbonyl compounds acetophenone, acrolein, and isophorone over Pt and Pd surfaces, we demonstrated that the lateral interaction between neighboring adsorbates can crucially affect their adsorption geometry and chemical transformations. Particularly acetophenone was observed to form dimers on the Pt surface above 136 K, which can either be present as ketone–ketone species or undergo keto–enol tautomerization and form ketone–enol dimers .…”
Section: Introductionmentioning
confidence: 93%
“…In our recent studies on hydrogenation of the simple carbonyl compounds acetophenone, acrolein, and isophorone over Pt and Pd surfaces, we demonstrated that the lateral interaction between neighboring adsorbates can crucially affect their adsorption geometry and chemical transformations. Particularly acetophenone was observed to form dimers on the Pt surface above 136 K, which can either be present as ketone–ketone species or undergo keto–enol tautomerization and form ketone–enol dimers .…”
Section: Introductionmentioning
confidence: 93%
“…Higher partial pressures of the reactant have also been shown to enhance the selectivity towards C=O bond hydrogenation . This effect was suggested to arise from increasing surface coverage, which causes the C=C group to become more tilted with respect to the surface and less vulnerable to attack by surface hydrogen atoms . The structure of the catalyst also critically influences the adsorption geometry of the reactant, and the selectivity of hydrogenation of α,β‐unsaturated ketones.…”
Section: Introductionmentioning
confidence: 97%
“…therein) that incorporate vdW forces in DFT electronic structure calculations, either through novel exchange-correlation functionals or as additional potential terms in the Kohn-Sham Hamiltonian. In surface science, these methods have been rather successfully used in describing multilayer systems involving graphene and boron-nitride [23], organic molecules adsorbed on metal [24][25][26][27][28][29][30][31][32][33][34][35][36][37] and nonmetal surfaces [38][39][40], graphene adsorbed on metal surfaces [41][42][43], and even organic molecules adsorbed on graphene adsorbed on metal surfaces [44]. These vdW methods have also been used to study the interaction of polyatomic [45][46][47] and diatomic [48][49][50] molecules with surfaces, and even with aromatic systems [51].…”
mentioning
confidence: 99%